Erectile dysfunction in men treated for testicular cancer. (June 2014) - Tal, Raanan; Stember, Doron S.; Logmanieh, Nina; Narus, Joseph; Mulhall, John P.
<x xml:space="preserve">Abstract</x> Objective To study the unique characteristics of erectile dysfunction (ED) in a population of men who developed ED after testicular cancer (TC) diagnosis and treatment. Patients and Methods All men treated for TC who presented for sexual function evaluation were included in an institutional database. All men underwent standard evaluation including a history/physical examination, completion of the International Index of Erectile Function (IIEF) questionnaire, testosterone/gonadotropin measurement and penile duplex Doppler ultrasonography (DUS). Results The study population comprised 76 men whose mean (sd) age was 29 (8) years and of whom 25% were married/had a partner. In all, 39% of the patients had seminoma and 61% had non‐seminomatous germ‐cell tumour (NSGCT). A total of 66% of patients with seminoma underwent radiation therapy. Of the patients with NSGCT, 79% received chemotherapy, 18% underwent primary retroperitoneal lymph node dissection (RPLND) and 20% underwent post‐chemotherapy RPLND. The mean (sd) time before seeking sexual medicine consultation was 12 (7) months after treatment completion, the median (range) number of vascular risk factors was 0 (0–2) and the mean (sd) remaining testis volume was 16 (8) mL. Mean (sd) total testosterone, luteinizing hormone, follicle‐stimulating hormone levels were 312 (186) ng/dL, 9 (7) IU/mL, 17 (12) IU/mL. A total of 26% of patients had total testosterone levels <300 ng/dL. In all, 84% of patients complained primarily of loss of erection‐sustaining capability and 24% had episodes of transient ED before TC diagnosis. The mean (sd) IIEF erectile function domain score was 16 (7). All the patients (100%) had a normal DUS. Mean (sd) peak systolic and end‐diastolic velocities were 48 (16) and 1.2 (2.2) cm/s, respectively. A total of 88% of patients responded to phosphodiesterase type 5 inhibitor (PDE5i) use with erections sufficient for penetration, but 12% did not (mean [sd] erectile function domain score 27 [5] vs 17 [6]). There were no differences in haemodynamics between those men with and without hypogonadism. Conclusions Men with TC presenting with ED after treatment appear uniformly to have normal erectile haemodynamics, suggesting adrenaline‐mediated ED. While the majority of TC survivors with ED respond successfully to PDE5i, a significant minority do not.